Evaluation of efficacy of microwave oven irradiation in disinfection of patient derived dental cast - Bhat, Vidya; Shenoy, Kamalakanth; Shetty, Shravan (International Journal of Infection Control, 2012)
Purpose: To check the efficacy of household microwave oven irradiation in disinfection of dental gypsum casts obtained from patients. Methodology: Impressions of upper arch of 10 volunteers were made using irreversible hydrocolloid. The casts were poured in type III gypsum. All casts were cut into two halves. One half of each cast was irradiated in a microwave oven , set at 650 W for a total of 3 minutes and the un-irradiated half was used as control. Suspension of casts was inoculated directly on Tryptone Soya Agar plates (TSA) by spread plate method. The inoculated plates were incubated aerobically at 32°C for 48 hours. Colonies grown on the agar plates were counted using a plate count reader. The data is presented as CFU/cast. Conclusion: 3 minutes microwave irradiation at 650 W is effective to reduce the microbial load of dental casts. Routine use of microwave for disinfection of cast could be recommended and used in between procedures to prevent cross contamination in the dental clinics.